Sinonasal Squamous Cell Carcinoma Survival Outcomes Following Induction Chemotherapy vs Standard of Care Therapy. (8th March 2022) - Murr, Alexander T.; Lenze, Nicholas R.; Weiss, Jared M.; Grilley‐Olson, Juneko E.; Patel, Shetal A.; Shen, Colette; Chera, Bhishamjit S.; Zanation, Adam M.; Thorp, Brian D.; Sheth, Siddharth H.
Abstract : Objective: To compare oncologic outcomes in sinonasal squamous cell carcinoma (SNSCC) treated with standard of care (SOC) definitive therapy, consisting of surgery or chemoradiotherapy, vs induction therapy followed by definitive therapy. Study Design: Retrospective review. Setting: Academic tertiary care hospital. Methods: The medical records of patients with biopsy‐proven SNSCC treated between 2000 and 2020 were reviewed for demographics, tumor characteristics, staging, treatment details, and oncologic outcomes. Patients were matched 1‐to‐1 by age, sex, and cancer stage according to treatment received. Time‐to‐event analyses were conducted. Results: The analysis included 26 patients with locally advanced SNSCC who received either induction therapy (n = 13) or SOC (n = 13). Baseline demographics, Charlson Comorbidity Index, and median follow‐up time were well balanced. Weekly cetuximab, carboplatin, and paclitaxel were the most common induction regimen utilized. Tolerance and safety to induction were excellent. Objective responses were observed in 11 of 13 patients receiving induction. No difference in disease‐free survival was found between the induction and SOC groups at 1 or 3 years. However, when compared with SOC, induction therapy resulted in significant improvement in overall survival at 2 years (100% vs 65.3%, P =. 043) and 3 years (100% vs 48.4%, P =. 016) following completion of definitive therapy. Two patients in the SOC group developed metastatic disease, as compared with none in the induction group. Conclusions: Induction therapy was safe and effective. When compared with SOC, induction therapy improved 3‐year overall survival.